2018
DOI: 10.1002/chem.201705981
|View full text |Cite
|
Sign up to set email alerts
|

2D and 3D Coordination Networks of Polynuclear Bismuth Oxido/Hydroxido Sulfonato Clusters from Low Temperature Solid‐State Metathesis Reactions

Abstract: Solid-state metathesis (SSM) reactions between Bi(NO ) ⋅5 H O and potassium benzene-1,2-disulfonate (=1,2-BDSK ), sodium benzene-1,3-disulfonate (=1,3-BDSNa ) allows access to the first 2D, {[Bi O (OH) (1-2BDS) (NO ) ⋅4 H O]⋅11 H O} and {[Bi O (OH) (1,3-BDS) ⋅12 DMSO]⋅3 DMSO⋅4 H O} , and 3D, {[Bi O (OH) (1,3-BDS) ⋅4 H O]⋅6 H O} , polymeric networks of sulfonato encapsulated polynuclear bismuth oxido/hydroxido clusters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 26 publications
0
10
1
Order By: Relevance
“…The cluster molecules do not interact with each other through coordinating bonds in the solid state (Figure ). This finding is in contrast to other bismuth oxido sulfonates such as the triflate, benzene‐1,2/1,3‐disulfonates, and 4,8‐disulfonyl‐2,6‐naphthalenedicarboxylates reported recently, which form polymeric networks in the solid state due to bridging sulfonato ligands.…”
Section: Resultscontrasting
confidence: 92%
See 1 more Smart Citation
“…The cluster molecules do not interact with each other through coordinating bonds in the solid state (Figure ). This finding is in contrast to other bismuth oxido sulfonates such as the triflate, benzene‐1,2/1,3‐disulfonates, and 4,8‐disulfonyl‐2,6‐naphthalenedicarboxylates reported recently, which form polymeric networks in the solid state due to bridging sulfonato ligands.…”
Section: Resultscontrasting
confidence: 92%
“…[Bi 9 O 7 (OH)(O 3 SCH=CH 2 ) 11 (dmso) 11 ](O 3 SCH=CH 2 )·3 DMSO (4) crystallizes in the triclinic space group P1 ,i nw hich the asymmetric unit comprises one molecule of cluster 4 ( Figure 5) 6 ], [72] [Bi 6 O 4 (OH) 4 (OTf) 6 (MeCN) 6 ], [49] and other sulfonates. [73] Three of the oxygen atoms are connected to one lateral bismuth atom each, located above the triangularf aces of the octahedron. This structure results in a m 4 -coordination of these oxygen atoms and a[ Bi 6 (m 3 -O) 4 (m 3 -OBi) 3 (m 3 -OH)] 12 + arrangement.…”
Section: Resultsmentioning
confidence: 99%
“…The so far unknown {Bi 6 O 4 (OH) 4 [OTf] 12 } 6– ([ BOT ] 6– ) cluster hexaanion formally consists of a cationic [Bi 6 (μ 3 -O) 4 (μ 3 -OH) 4 ] 6+ core surrounded by 12 triflate anions. In the core, which is a common motif in hydrolysis products of bismuth salts, six bismuth­(III) centers occupy the corners of an octahedron, whose faces are capped by four oxo and four hydroxo ligands in a μ 3 fashion (the hydroxy protons could not be located crystallographically). The 12 edges of the octahedron are each capped by a triflate anion in a μ 2 -O fashion, six of which form the ring arrangement shown in Figure b.…”
Section: Resultsmentioning
confidence: 99%
“…Compound 6 ([Bi 6 O 4 (OH) 4 (H 2 O) 12 (H 2 DSNDC) 3 ]· x H 2 O) crystallizes in the triclinic space group P 1̅. The three Bi 3+ ions and their symmetry equivalents form the well-known {Bi 6 O 4 (OH) 4 } cluster, which was even observed in two-dimensional and three-dimensional CPs. , The O 2– and OH – ions are disordered and could not be refined separately. Six different linker molecules coordinate to one cluster and connect each of the IBUs to four others.…”
Section: Resultsmentioning
confidence: 99%
“…While the Bi–O clusters and dinuclear IBUs are mostly formed through reactions at room temperature or hydrolysis at moderate temperatures, respectively, the Bi–O chains were mostly obtained by hydrothermal synthesis. A large diversity of reaction methods have been employed to study these compounds, e.g., slow solvent evaporation or diffusion of solvent, hydrolysis, solvothermal and ionothermal reactions, and solid-state metathesis using reaction temperatures between −28 and +180 °C and reaction times of a few minutes up to several days. Unfortunately, only very few systematic multiparameter studies on the product formation have been reported today; hence, bismuth CPs seem to be perfectly suited for these investigations.…”
Section: Introductionmentioning
confidence: 99%